Model Komunikasi Tokoh Masyarakat Dalam Menanggulangi Aksi Premanisme Di Kecamatan Medan Amplas Sumatera Utara - Juhari; Ulil Amri Nasution (Program Studi Komunikasi dan Penyiaran Islam, 2025)
This research was conducted in response to the frequent occurrences of thuggery (premanism) in Medan Amplas District, North Sumatra. Such actions have been considered to violate moral norms, legal norms, and religious values, and have generated social discomfort within the community. Previous efforts to address thuggery have predominantly relied on repressive approaches, causing perpetrators to cease their actions only temporarily while seeking other opportunities and ways to continue them. This research employed a qualitative approach and collected data through in-depth interviews with several informants who were considered to have the capacity to provide relevant information. The findings indicate that the communication model implemented by community leaders in Medan Amplas possesses strategic value in addressing acts of thuggery occurring in their social environment.